218k views
1 vote
Find y'' of
y=7x^8/7-5x^1/6

User Tbaranes
by
4.7k points

1 Answer

5 votes

Answer:

Explanation:

Use the power rule of differentiation:


x^n=nx^n^-^1\\7*(8)/(7) x^(1)/(7) =8x^(1)/(7) \\-5*(1)/(6) x^(-5)/(6) =-(5)/(6) x^(-5)/(6) \\8x^(1)/(7) -(5)/(6) x^(-5)/(6) =y'

Now take the derivative of that function:


8*(1)/(7) x^(-6)/(7) =(8)/(7) x^(-6)/(7) \\-(5)/(6) *(-5)/(6) x^(-11)/(6) =(25)/(36) x^(-11)/(6)\\(8)/(7) x^(-6)/(7) +(25)/(36) x^(-11)/(6) =y''

Now simplify:


\frac{8}{7\sqrt[7]{x^6} } +\frac{25}{36\sqrt[6]{x^1^1} } =y''

User Armulator
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.